THE IMPACT OF PRICE PERCEPTION AND BRAND IMAGE ON BEHAVIORAL LOYALTY OF INNISFREE SKINCARE CONSUMERS - Nurdin, Vinny; Simamora, Bilson (AIBPM Publisher, 2023)
Innisfree is one of the well-known brands originating from South Korea with products that have natural ingredients originating from Jeju Island. In the context of Innisfree, researchers want to study price and brand image perceptions of behavioral loyalty. The aims of this study were to find out (1) how price perceptions affect behavioral loyalty to Innisfree skin care products and (2) whether brand image affects consumer behavior loyalty to Innisfree skin care products. Based on the findings from the research that has been done, the results show that price perception has a positive and significant effect on behavioral loyalty and brand image has a positive and significant effect on behavioral loyalty. Suggestions that can be given to companies are that companies are encouraged to consider making Innisfree products at more affordable prices, making other product variations that are suitable for use by consumers who have acne and oily skin problems, and for future researchers to look for different variables. that can affect the repurchase of a product.